Analisis Pentingnya Disiplin Kerja, Lingkungan Internal dan Kepuasan Karyawan Terhadap Produktivitas Kerja Karyawan - Desi Novita Rini Pandiangan; Purnama Yanti Purba; Rismawati Waruwu; Jhonsen Jhonsen; Novy Rachma Herawati (Journal of Management and Bussines (JOMB), 2023)
This research aims to test and analyze the influence of Work Discipline, Internal Environment, and Employee Satisfaction on Employee Work Productivity. The research method used is quantitative. The nature of the research used is descriptive explanatory. The sampling technique used was simple random sampling. The total sample was 99 people. The data analysis method is multiple linear regression. The research results show that partially and simultaneously work discipline, internal environment and job satisfaction have a positive and significant effect on employee work productivity. The conclusion of the research is that improving employee work discipline, internal environment and employee satisfaction can encourage high employee work productivity. Keywords: Discipline, Satisfaction, Internal Environment, Productivity